Autism Spectrum Disorders and inclusion attitudes in the Italian school environments: teachers’ knowledge, attitudes, perceptions and their necessity to consult a healthcare multidisciplinary team. - Conte, Luana; Lupo, Roberto; Mazzarella, Chiara; Calabrò, Antonino; Vaglio, Laura; Chirizzi, Sandro; Donadio, Carmen; Carvello, Maicol; Marsella, Alessandra; Artioli, Giovanna; Vitale, Elsa (Acta Biomedica Atenei Parmensis, 2022)
Background: Schools play a key role in detecting early signs of autism and creating a targeted pathway of study and inclusion. This becomes complicated when faced with unknown situations, such as managing a student with Autism Spectrum Disorders (ASD).Materials and Methods: A nationwide study involving teachers (n=235) was conducted from March to August 2021. The survey instrument consisted of a questionnaire administered online through social networks containing socio-demographic data, attitudes, knowledge and inclusion plans from school teachers towards students with ASD.Results: Statistical significant differences were registered for the item no.13: among the main deficits caused by ADS are reduced social cognition, language abnormalities, and impaired sensory functioning. (p=.025); the item no.8 (p=.011): if an intervention works for one child with ASD, it is certain to work on another child with ASD; the item no.3(p=.002): genetic factors play an important role in the causes of ASD. By also considering teacher’s attitudes towards ASD according to the presence of a healthcare worker in the school environment, significant differences were registered for the item no.1 (p=.032): the interpretation that the diagnostic criteria for Asperger's syndrome are the same as for high-functioning autism; the item no.6 (p=.025): children with ADS are very similar to each other, and the item no.7(p=.015): early intervention does not lead to additional benefits for children with ASD.Conclusions: The presence of professionals with advanced skills could be a benefit and represent a strong point in the application of measures of prevention and containment of community pathologies.